PARADOX OF BUREAUCRACY NEUTRALITY IN THE INDONESIA REGIONAL ELECTION - Tamma, Sukri (PALITA, 2016)
AbstractThis paper aim provides how the actual issue of neutrality of Indonesian bureaucracy,especially on the Civil Servants of local government related to the Local election process. Theimportant position of civil servants as public servants with its network touches many aspects ofcommunity life makes people as dependent on the bureaucracy existence. At the same time,bureaucracy seems under the politicians interests due to their position in the system ofregional government. This study also simultaneously shows how the concept of neutralityimplements in Indonesian bureaucracy associated with the Indonesian political system,including in the context of the regional government.